Dimerization of Peptides by Calcium Ions: Investigation of a Calcium-Binding Motif. (11th September 2014) - Jamalian, Azadeh; Sneekes, Evert-Jan; Dekker, Lennard J. M.; Ursem, Mario; Luider, Theo M.; Burgers, Peter C.
Abstract : We investigated calcium-binding motifs of peptides and their recognition of active functionalities for coordination. This investigation generates the fundamentals to design carrier material for calcium-bound peptide-peptide interactions. Interactions of different peptides with active calcium domains were investigated. Evaluation of selectivity was performed by electrospray ionization mass spectrometry by infusing solutions containing two different peptides (P1 and P2 ) in the presence of calcium ions. In addition to signals for monomer species, intense dimer signals are observed for the heterodimer ions( P 1 ⋯ C a 2 + ⋯ P 2 ) (⋯ represents the noncovalent binding of calcium with the peptide) in the positive ion mode and for ions( P 1 - 2 H 2 - ⋯ Ca 2 + ⋯ P 2 - 2 H 2 - ) in the negative ion mode. Monitoring of the dissociation from these mass selected dimer ions via the kinetic method provides information on the calcium affinity order of different peptide sequences.